Social Media and Online Prostitution Industries - Khafit Badrus Zaman; Ardiansyah, Mohammad Iqbal Firman; Muhammad Busthomi Arviansyah; Muhammad Ferdyan Syach; Naziro; Aji Prasetya Wibawa (Association for Scientific Computing Electrical and Engineering, 2022)
Online prostitution continously increases along with the development of technology and information. This study aims to observe the development of prostitution globally, including the developed countries and developing countries. This research was conducted by collecting the world data news about online prostitution in the last ten years (2011-2021). Most of the motives of online prostitution are economic factors. Several online prostitution cases involved minors. Online prostitution cases in developed countries and developing countries occur on several social media platforms such WeChat, LINE, MiChat, and Facebook. In the discussion chapter, the writers provide suggestions to minimize the cases of online prostitution which one of them is making regulations to govern the use of social media.